The Urgency of Reconstructing Indonesia's Justice System Towards Recognition of Customary Justice Institutions - Stefany Ismantara (West Science Law and Human Rights, 2023)
The 1945 Constitution acknowledges and protects the existence of indigenous communities. However, the existence of customary court has been abolished through Emergency Law No. 1/1951, and its legal authority is still not recognized to this day. This creates ambiguity in the administration of the justice system. Therefore, an assessment of the urgency of reconstructing Indonesia's justice system to achieve recognition of customary justice institutions is needed. In addressing this, there is a need to answer the issues concerning customary court and how the state can reconstruct the justice system. The author employs a normative legal research method with a qualitative and case study approach through literature review. Through this method, it is found that non-binding legal force of customary court decisions leads to negative consequences for indigenous people and customary law itself. Therefore, a strong legal framework is required through the enactment of the Indigenous Community Bill. Collaboration between law enforcement and indigenous people is also essential in resolving indigenous cases.